2009
DOI: 10.1021/ja9035362
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Ladderphanes

Abstract: A new class of polymers, which have a double-stranded polybinorbornene skeleton with multilayer planar oligoaryl linkers, defined as polymeric ladderphanes, are synthesized. The structures of these ladderphanes are determined by spectroscopic means. Photophysical studies and time-resolved fluorescence spectroscopic investigations reveal that there is a strong interaction between the chromophore linkers. Thus, Soret band splitting in the absorption spectrum of the polymer with porphyrin linker (12e), significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 81 publications
3
91
1
1
Order By: Relevance
“…and DNA complex [54,55] can be characterized through electrophoretic translocation in a nanopore. It was demonstrated that the capture rate in the translocation processes can be enhanced or manipulated by diffusiophoresis [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…and DNA complex [54,55] can be characterized through electrophoretic translocation in a nanopore. It was demonstrated that the capture rate in the translocation processes can be enhanced or manipulated by diffusiophoresis [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(dibenzofulvene)s, 4-11 7,7-diarylnorbornane-containing conjugated polymers, 12,13 cyclophanecontaining polymers and face-to-face ferrocene polymers [36][37][38] have been synthesized, and their optical and electrochemical properties have been studied in detail. Polymers with layered aromatic rings and p-electron systems have also been investigated; [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] for example, Chen et al 53 recently reported the synthesis and formation of a twodimensional assembly of polymeric ladder phanes containing face-toface p-electron systems. These polymers have potential applications in optoelectronic devices and single-molecular devices such as singlemolecular wires.…”
Section: Introductionmentioning
confidence: 99%
“…Making the pore smaller to favor the entry of a DNA end relative to folded or tagged DNA minimizes the folding issue but can reduce the rate of DNA capture into the pore and adversely affect throughput. The process of DNA capture into a pore as a function of DNA length, salt concentration and gradient, voltage, pore size, and other factors has been examined in depth from both experimental and theoretical perspectives [32,[49][50][51][52][53]. Varying the salt and voltage conditions alters the rate of DNA capture and its dependence on length and other factors.…”
Section: Dna Capturementioning
confidence: 99%